PENGARUH PEMAKAIAN POD COKLAT SEBAGAI ' PENGGANTI' JAGUNG' DALAMRA.NStiM'·' TERHADAPPERTAMBAHANBOBOTBADANDAN EFISIENSI PENGGUNAAN RANSUM PADA SAPI BRAHMAN CROS$ - Dewi Ananda Mucra (Jurnal Peternakan, 2005)
This research was conducted, to know the effect of used cocoa pod to subtitude com in Brahman Cross ration to determine weigh gain and ration efficiency of 12 bulls Brahman Cross. Method of research was completely randomized design into 4 treatments with cocoa pod level 0%, 4.80%, 9.60% and 14.40% to subtitute com in dry matter ration and three replication.Parametres identified were dry matter feed in take, weigh gain and ration efficiency. Result showed that there were non significant (P > 0.(5) effect between treatment or parametres identified, so that cocoa pod can used 100% to subtitute com in Brahman Cross ration. '